1999
DOI: 10.1071/a98138
|View full text |Cite
|
Sign up to set email alerts
|

Effects of superphosphate fertiliser and stocking rate on the nutritive value of perennial ryegrass and subterranean clover herbage

Abstract: The effect of superphosphate fertiliser on digestible dry matter (DDM) and crude protein (CP) percentages of perennial ryegrass and subterranean clover was assessed on a long-term, grazed experiment in western Victoria. CP of both species increased significantly (3–6 units) where long-term average phosphorus (P) applications were 33 kg/ha.year compared with 1 kg/ha.year. CP of herbage was also greater on paddocks grazed at higher (9–23 ewes/ha) than lower (5–13 ewes/ha) stocking rates (1–3 units). DDM of subte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 0 publications
3
11
1
Order By: Relevance
“…The relationship between dietary intake and grazing management has been explored for cattle by McCollum et al (1994) who found, in a comparison of short-duration grazing with different graze and rest periods, that diet composition had a higher, more stable plane of nutrition when grazing periods were more frequent compared with slower rotational grazing. The influence of the higher level of soil fertility and pasture renovation on farmlet A on the level of digestibility of the herbage was substantial and is consistent with the findings from a longterm experiment in western Victoria (Saul et al 1999). They found that high rates of fertiliser (up to 33 kg/ha of phosphorus) were responsible for significantly increasing the digestible DM of the clover and volunteer components of the pasture and noted the importance of monitoring nutritive value because of its substantial flow-on effects for animal production per head and per hectare.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The relationship between dietary intake and grazing management has been explored for cattle by McCollum et al (1994) who found, in a comparison of short-duration grazing with different graze and rest periods, that diet composition had a higher, more stable plane of nutrition when grazing periods were more frequent compared with slower rotational grazing. The influence of the higher level of soil fertility and pasture renovation on farmlet A on the level of digestibility of the herbage was substantial and is consistent with the findings from a longterm experiment in western Victoria (Saul et al 1999). They found that high rates of fertiliser (up to 33 kg/ha of phosphorus) were responsible for significantly increasing the digestible DM of the clover and volunteer components of the pasture and noted the importance of monitoring nutritive value because of its substantial flow-on effects for animal production per head and per hectare.…”
Section: Discussionsupporting
confidence: 73%
“…On the other hand, the accumulation of surplus herbage found on farmlets B and C resulted in carry-over of dead residual material, which can make it more difficult for a grazing animal to select a diet of sufficient quality. The fact that farmlet A showed significantly higher herbage quality than farmlets B and C, even though the grazing management on A and B was the same, confirms the substantial influence of the combination of higher soil fertility levels, the sowing of temperate pasture species and the higher stocking rate on enhancing pasture quality, as found by others (Saul et al 1999). This is likely to be the principal reason that farmlet A was able to support more stock without penalties in per head performance over a period of several years even though, at times, more supplement was needed on this farmlet .…”
Section: Discussionsupporting
confidence: 64%
“…The improved quality of feed on offer is a result of changes in both botanical composition and improvements in the DM digestibility and crude protein content of the grasses and legumes found within the sward, as well as the pastures' response to utilisation (Saul et al 1999). The maintenance of soil fertility has also been shown to be necessary for the persistence and productivity of introduced and desirable species and to slow the ingress of less desirable species (Cook et al 1978a;Garden and Bolger 2001).…”
Section: The Cicerone Project Farmlet Experimentsmentioning
confidence: 99%
“…Increases in the productivity of grazing enterprises from the application of fertiliser have occurred due both to increases in the growth rate of pastures, including newly established, as well as naturalised and native pastures, and improvements in the quality of the feed on offer for ruminant production (Sale and Blair 1997;Saul et al 1999). The improved quality of feed on offer is a result of changes in both botanical composition and improvements in the DM digestibility and crude protein content of the grasses and legumes found within the sward, as well as the pastures' response to utilisation (Saul et al 1999).…”
Section: The Cicerone Project Farmlet Experimentsmentioning
confidence: 99%
“…With its greater level of temperate species (Shakhane et al 2013b) and higher soil fertility, farmlet A had significantly higher digestibility levels, resulting in a higher level of green digestible herbage over much of the experiment (Shakhane et al 2013a). Digestible herbage is known to be increased substantially by higher concentrations of soil phosphorus and sulfur, resulting in increased animal production (Saul et al 1999).…”
Section: Herbage Mass and Qualitymentioning
confidence: 99%